Development of Science Storybook Based on Metro City Cultural Heritage as Integrated Literacy Media for Science and Indonesian Language in Elementary School - Muhamad Alfarisi; Rizka Ahmad Maulana; Ade Gunawan; Dimas Bagus Editya (IJECA (International Journal of Education and Curriculum Application), 2026)
This study aims to develop and evaluate a Metro City cultural heritage-based science storybook as integrated literacy media for science and Indonesian language learning in elementary school. The development employed the Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), involving expert validators, readability testing participants, and 90 fourth-grade students across three schools for quasi-experimental field testing. Results showed that the storybook met very valid criteria based on expert validation (material 90.4%, language 89.6%, media 91.2%) and achieved a very practical readability rating. Field testing demonstrated significant learning improvements, with the experimental group attaining high N-Gain scores of 0.74 (scientific literacy) and 0.71 (Indonesian language), compared to 0.42 and 0.41 in the control group, supported by very large effect sizes (Cohen's d = 1.92 and 1.67). This study contributes a novel triple integration model that connects science concepts, Indonesian language genres, and local cultural heritage within a unified elementary thematic learning medium.